Sociolinguistic, morphosyntactic, semantic and stylistic gender detection-oriented comparative analysis of opening and topic sentences of an article published by The Guardian, The Daily Mirror, The Telegraph and The Independent - Majetic, Senka (Eximia, 2023)
Comparative analysis of a daily news published by The Guardian, The Daily Mirror, The Telegraph and The Independent is a short discussion on syntactic and semantic variabilit(ies). The comparison between the four includes an overview of the morphosyntactic operator, semantic operator, female language parameters operator analysis of opening and topic sentence. This article might be useful as an insight into corpus analysis of newspaper discourse. It is also a confirmation of the null hypothesis: Female language dominates in natural disaster reports! Due to the skimming and scanning current habits opening and topic sentence analysis has been done!